FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PENGUNJUNG TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS LUBUK BEGALUNG PADANG TAHUN 2016 - Murni ati (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Visitor satisfaction refers to responses to customer expectations before and afterreceiving the service. The public health services have visit numbers decrease every year. Theincidence can be attributed to the dissatisfaction of visitors to the services provided. The type ofresearch iwas descriptive analytic, the population is was the old visitors (repeated). The numberof samples was 87 people from the total population of 733 visits by sampling technique AccidentalSampling. The data collection using questionnaire data instrument was analyzed by univariat andbivariate. The results obtained 47.1% of visitors were less satisfied with the health service. Lessthan 3 states express less good on the Reliability, Assurance and Tangible dimensions. A smallpercentage of visitors expressed less well on the Empathy and the Responsiveness dimensions.There was a significant relationship between Assurance dimension, Tangible with visitorsatisfaction. There was no significant relationship between the dimensions of Reliability, Empathyand Responsiveness with visitor satisfaction. Puskesmas Lubuk Begalung Padang has to createpolicies to improve the quality of health services by motivating officers to carry out timely serviceschedule, pay attention and respond to complaints to serve visitors with courtesy and friendly,maintain and improve the cleanliness and comfort of the room, and provide clear and easy tounderstand information for visitors.Key words: visitor satisfaction, health service, Public Health Services (Puskesmas)